(untitled) (DEPAN, 2025)
Purpose: This study examines the impact of financial literacy on the investment decisions of investors in Nepal’s share market. It emphasizes the ability of individual investors to make informed financial choices, manage savings, assess risk tolerance, and select suitable investment opportunities. Methodology: A descriptive and causal-comparative research design was employed for this study. Data were collected via investment-related questionnaires distributed among individual investors in the Kathmandu Valley. Statistical analysis was conducted using regression and correlation analysis to explore the relationships between financial knowledge, personal savings, risk tolerance, investment options, and investment decisions, using SPSS software for data interpretation. Results: The findings indicate a positive correlation between financial literacy and investment decisions. Enhanced financial education alongside increased risk tolerance leads to more informed and strategic investment choices. Additionally, the study found that higher individual savings and a broader range of investment options contribute positively to financial outcomes. Discussion: The study highlights the critical role of financial literacy in empowering investors to manage their finances effectively and meet their investment goals. It suggests the development of policy frameworks aimed at instituting financial education schemes to foster a robust investment culture, enhance market participation, and spur economic growth in Nepal. Conclusion: The research underscores the necessity for increasing financial literacy among investors in Nepal, pointing to its significant impact on investment strategies and overall financial health. Implementing educational programs can facilitate better financial decision-making and contribute to a thriving economy. Novelty: This study uniquely explores the impact of financial literacy on investment decisions within the under-researched context of Nepal’s share market. It employs strong methodological techniques to analyze the interrelationships between financial knowledge, risk tolerance, and savings management.